Arctic ungulates at the northern edge of terrestrial life - Klein, David R. (Rangifer, 1996)
The two ungulate species that occur in the High Arctic, Rangifer tarandus and Ovibos moschatus, exhibit considerable adaptive plasticity in response to habitat variability throughout their circumpolar distribution. R. tarandus, however, has a much wider latitudinal distribution and occurs within a wider range of both forest and tundra habitat types than 0. moschatus, reflecting greater morphological, physiological, and behavioral plasticity. As a consequence, muskoxen have been less successful than caribou and reindeer in maintaining populations at their southern limits. Muskoxen, however, existed throughout Pleistocene glaciations in the cold periglacial steppes of Eurasia and North America and find the closest analog to this vegetation type in the High Arctic, where they have been more successful than R. tarandus in maintaining their populations.